Peningkatan Hasil Belajar Barisan Aritmatika Siswa SMK Melalui Pembelajaran Open Ended Problems - Putri, Like Rizky; Hima, Lina Rihatul; Santia, Ika (Polinomial : Jurnal Pendidikan Matematika, 2025)
This study aims to improve students’ learning outcomes in arithmetic sequences through the implementation of the open-ended problems learning model. The background of the research highlights students' difficulties in understanding mathematical concepts, particularly arithmetic sequences, due to teacher-centered learning methods and limited student engagement. A total of 88.88% of students in class X-TKJ at SMK Arrahmah Papar did not meet the Minimum Mastery Criteria (KKM) of 75 in the Mid-Semester Exam. The open-ended problems approach was chosen based on its proven effectiveness in enhancing students' critical and creative thinking skills (Nazareth & Mukhlis, 2022). This study used a quantitative approach with a One Group Pretest-Posttest Design. The research subjects consisted of 36 students. Data were collected through mathematics pretest and posttest, teacher observation sheets, and student response questionnaires. The results showed a significant improvement in learning outcomes, with the average score increasing from 61.39 (pretest) to 82.36 (posttest). The Paired Sample t-test yielded a significance value of 0.000 (< 0.05), indicating a significant difference between pretest and posttest scores. Teacher activity was rated very good with an average of 88.15%, while student responses were positive with an average of 81.18%. The study concludes that the open-ended problems learning model is effective in improving both the learning outcomes in arithmetic sequences and students’ critical and creative thinking abilities